Comparative Study of Hydroxytyrosol Acetate and Hydroxytyrosol in Activating Phase II Enzymes - Xuan Zou; Mengqi Zeng; Yuan Zheng; Adi Zheng; Li Cui; Wenli Cao; Xueqiang Wang; Jiankang Liu; Jie Xu; Zhihui Feng (Antioxidants, 2023)
Nuclear factor E2-related factor 2 (Nrf2) is fundamental to the maintenance of redox homeostasis within cells via the regulation of a series of phase II antioxidant enzymes. The unique olive-derived phenolic compound hydroxytyrosol (HT) is recognized as an Nrf2 activator, but knowledge of the HT derivative hydroxytyrosol acetate (HTac) on Nrf2 activation remains limited. In this study, we observed that an HT pretreatment could protect the cell viability, mitochondrial membrane potential, and redox homeostasis of ARPE-19 cells against a t-butyl hydroperoxide challenge at 50 μM. HTac exhibited similar benefits at 10 μM, indicating a more effective antioxidative capacity compared with HT. HTac consistently and more efficiently activated the expression of Nrf2-regulated phase II enzymes than HT. PI3K/Akt was the key pathway accounting for the beneficial effects of HTac in ARPE-19 cells. A further RNA-Seq analysis revealed that in addition to the consistent upregulation of phase II enzymes, the cells presented distinct expression profiles after HTac and HT treatments. This indicated that HTac could trigger a diverse cellular response despite its similar molecular structure to HT. The evidence in this study suggests that Nrf2 activation is the major cellular activity shared by HTac and HT, and HTac is more efficient at activating the Nrf2 system. This supports its potential future employment in various disease management strategies.